Harnessing Hyperthermia: Molecular, Cellular, and Immunological Insights for Enhanced Anticancer Therapies - Lukácsi, Szilvia; Munkácsy, Gyöngyi; Győrffy, Balázs (Integrative cancer therapies, 2024)
Hyperthermia, the raising of tumor temperature (≥39°C), holds great promise as an adjuvant treatment for cancer therapy. This review focuses on 2 key aspects of hyperthermia: its molecular and cellular effects and its impact on the immune system. Hyperthermia has profound effects on critical biological processes. Increased temperatures inhibit DNA repair enzymes, making cancer cells more sensitive to chemotherapy and radiation. Elevated temperatures also induce cell cycle arrest and trigger apoptotic pathways. Furthermore, hyperthermia modifies the expression of heat shock proteins, which play vital roles in cancer therapy, including enhancing immune responses. Hyperthermic treatments also have a significant impact on the body’s immune response against tumors, potentially improving the efficacy of immune checkpoint inhibitors. Mild systemic hyperthermia (39°C-41°C) mimics fever, activating immune cells and raising metabolic rates. Intense heat above 50°C can release tumor antigens, enhancing immune reactions. Using photothermal nanoparticles for targeted heating and drug delivery can also modulate the immune response. Hyperthermia emerges as a cost-effective and well-tolerated adjuvant therapy when integrated with immunotherapy. This comprehensive review serves as a valuable resource for the selection of patient-specific treatments and the guidance of future experimental studies.